2001
DOI: 10.1080/09523980110041944
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Technology in Teaching and Teacher Education: Implications for Policy and Curriculum Reform

Abstract: This paper discusses technology integration in teaching and teacher education. Emphasis is placed on policy and curriculum reform as they relate to the use of information technologies for teacher education. Particular reference is made to the situation in Cyprus public schools. It is argued that for successful technology integration, there needs to be a shift in pedagogical approaches and reform of teacher education programmes. Concluding, suggestions are provided on how information technologies can best be in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 13 publications
(2 reference statements)
0
33
0
6
Order By: Relevance
“…So the present study revealed that the teachers were not able to recognise efficient multimedia learning materials. Vrasidas and McIsaac (2001) wrote that teacher education programmes play a crucial role for technology-based teaching and learning across the various disciplines. Today's teachers should be able, besides utilising other teaching skills, to utilise instructional technology, particularly computer-based technologies.…”
Section: Resultsmentioning
confidence: 99%
“…So the present study revealed that the teachers were not able to recognise efficient multimedia learning materials. Vrasidas and McIsaac (2001) wrote that teacher education programmes play a crucial role for technology-based teaching and learning across the various disciplines. Today's teachers should be able, besides utilising other teaching skills, to utilise instructional technology, particularly computer-based technologies.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with Vrasidas and McIsaac (2001), technology is a tool that students use to construct knowledge and share their understanding of content. As a result, students' exposure to technological improvements has influenced their learning approaches and expectations on the services that should be made available to them (Hechanova & Cementina-Olpoc, 2013;Zandvleit & Fraser, 2004).…”
Section: Technologymentioning
confidence: 99%
“…Sansone and Harackiewicz (2000) suggest a basic classification of motivation, as intrinsic or extrinsic, such that intrinsic motivation concerns active engagement with tasks that people ISSN 2330-9709 2015 find interesting and that, in turn, promote growth (Ryan & Deci, 2000). Furthermore, intrinsically motivated students construct their own meanings and understanding on the basis of their prior experiences, according to a constructivist approach (Vrasidas & McIsaac, 2001). That is, during the learning process, students compare what they are learning with what they know about a specific topic, and then decide whether to accept the new knowledge or hold fast to what they already know.…”
Section: Intrinsic Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer drills take place 40 minutes per week. Integrating computers into the teaching is a very important subject to which some of the teachers were introduced during their training (Vrasidas & McIsaac, 2001;Perkins, 1992). Mevarech and Rich (1985) examined student achievement in math in schools in disadvantaged areas using the Ministry of Education test from 1977.…”
Section: The Computer As a Tool For Improving Math Teachingmentioning
confidence: 99%